Executive control influences linguistic representations. - Lev-Ari, Shiri; Keysar, Boaz (Memory & Cognition, 2014)
Although it is known that words acquire their meanings partly from the contexts in which they are used, we proposed that the way in which words are processed can also influence their representation. We further propose that individual differences in the way that words are processed can consequently lead to individual differences in the way that they are represented. Specifically, we showed that executive control influences linguistic representations by influencing the coactivation of competing and reinforcing terms. Consequently, people with poorer executive control perceive the meanings of homonymous terms as being more similar to one another, and those of polysemous terms as being less similar to one another, than do people with better executive control. We also showed that bilinguals with poorer executive control experience greater cross-linguistic interference than do bilinguals with better executive control. These results have implications for theories of linguistic representation and language organization.